Site occupancy and mechanisms of thermally stimulated luminescence in Ca9Ln(PO4)7 (Ln=lanthanide) - Bessière, Aurélie; Benhamou, Rajia Aït; Wallez, Gilles; Lecointre, Aurélie; Viana, Bruno (Acta materialia, 2012)
The structural properties, X-ray-excited radioluminescence and thermally stimulated luminescence (TSL) of Ca9Ln(PO4)7 (Ln=La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu) were investigated. (La–Nd) occupied mainly the largest M3 site, whereas the smallest lanthanides (Yb, Lu) adopted the smallest octahedral M5 site. The intermediate-sized ions (Sm–Tm) occupied the medium-sized sites M1 and M2. Only the Ln3+ ions with the highest Ln3+/4+ ionization energy (Ln=Pr, Nd, Tb, Dy) were able to trap holes and become luminescent centers for thermally stimulated Ln3+ 4f–4f emission. For low Ln3+/4+ ionization potential (Ln=La, Gd, Yb, Lu), no hole trapping at Ln3+ was possible and Mn2+ impurities at the M5 sites were the effective hole traps and luminescent centers for thermally stimulated Mn2+ 3d–3d red emission. Very broad TSL peaks were attributed to thermally assisted detrapping of electrons from positive traps, possibly Ln3+ at Ca2+ sites, tunneling back towards the hole trap/luminescent center. Ca9Ln(PO4)7 compounds doped with Ln=Tb or Lu were found to be efficient X-ray-excited long-lasting phosphorescence materials, emitting in the green and in the red, respectively.